Netherton Syndrome in Combination with Iron-deficiency Anemia - Ekaterina Orlova (Journal of Global Pharma Technology, 2016)
Netherton syndrome (NS) is a rare severe autosomal recessive disorder of cornification characterized by a triad of symptoms: congenital ichthyosiform erythroderma, trichorrhexis invaginata and an atopic diathesis with elevated immunoglobulin E (IgE). Skin surface recovered in the background of IDA correction with iron preparations and vitamin and mineral complexes. Family history: patient has a 55-year-old uncle with ichthyosis vulgaris and her 4-year-old daughter suffers atopic dermatitis. The patient was treated with systemic steroids (prednisolone solution 90mg per day IV days 1-5; 60 mg per day, days 6-11; 30 mg per day, days 12-15) with marked improvement of the skin lesions in 1, 5 weeks. At the time of discharge from the hospital almost complete regression of eruptions and desquamation was observed, there were some residual effects in the form of post-inflammatory erythema. We present a case of a 29-year-old woman with Netherton syndrome, primarily diagnosed with atopic dermatitis. The iron-deficiency anemia concurrent with gastro-intestinal tract disorder was also observed. Topical corticosteroid therapy showed no clinical improvement. Combined in-depth clinical assessment and genetic testing resulted in NS diagnosis with subsequent successful systemic therapy-intestinal tract. Trichoscopy examination of the scalp hair demonstrated trichorrhexis nodosa, one of the typical NS signs. Initial parameters. HGB: 95.0g/l (normal range 120-140g/l), RBC: 3.451012/l; (normal range 3.7-4.71012/l), Hypochromia: ++ Color indicator: 0.64 (normal range 0.85-1.15), Eosinophils 13%; (normal range 0-5) and serum IgE level of 156 IU/ml (normal range 20-100 IU/ml). Quality blood indicators after treatment are within normal limits or close: HGB level has increased, eosinophils number has decreased, which indicates an almost complete inflammatory process cessation in the body. The main change vital for the body, which the physiological blood indicators depend on, is an increase in iron content (almost 1.5 times). Indicators of toxic substances, such as uric acid, decreased. Each of the patients with Netherton's syndrome requires a strictly individual approach. Emphasis on the advisability of prescribing systemic glucocorticosteroids is also essential, as well as the dosage of aromatic retinoids. In this case, the dosage and prescription of drugs of this type depends on the disease severity, in particular on the pathology’s manifestations on the skin surface. Genetically caused disease (Netherton syndrome) proceeded against the background of acquired disease (anemia). Our strategy has shown effectiveness, caused by systemic steroids.Key words: Netherton syndrome, Trichorrhexis invaginata, Ichthyosiform erythroderma, SPINK 5, Iron-deficiency anemia.